(3CMcGe GdaUhd aj CMcGe GdCUhds - (3SdjeGf Hf Nda Hf SYO GdJLjHj GdbQWHj, CHh GdhdjO GdHGLj,J (B474 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CQTOfG Edi efGgL SHdg CeG HYO Cf CLeY dc cJGHkG ai CUhd Gdabg aUd ai HjGf GdMOhO GdJi jMJGL EdjgG s
(3BNQgG (B:s
(3hLhGH BNQ hgh Cf GdJZdjH hGdSQGjI EfeG JMUd HYO hbhYg hfMf afGRY ai hbhYg ajHWd eG bGdhg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B261s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs